The Influence of Brand Image and Buzzer Messages on Buying Interest in Tiktok - Firdaus, Yasinta' Rachmi (Proceeding of International Management Conference and Progressive Papers, 2024)
The rapid advancement of technology and social media has changed the way consumers interact with brands, with TikTok emerging as a key marketing platform, especially among young audiences. According to Keller (in Dam 2021) the mental relationship between consumers and brands is very important in forming a brand image, meeting consumer expectations, and differentiating the company thereby increasing sales potential. This study explores the influence of brand image and buzzer messages on purchase intentions in TikTok to address the research gap in the Indonesian market. As stated by Hawkins and Mothersbaugh (in Vivian, 2020), brand image includes the target market's interpretation of the product's benefits and usage attributes, while Lin et al. (2021) argue that brand image can be assessed through brand quality, consistency and personality. Meanwhile, buzzer messages effectively shape consumer engagement and purchase intentions through impactful social media content as stated by (Arum 2021) and Rifda (2022). This quantitative study surveyed 97 purposefully selected TikTok users aged 14-60 years who had made purchases through the TikTok Shop. Statistical analysis including multiple linear regression was used to assess the influence of brand image and buzzer messages on purchase intention. This research shows that brand image has no effect on purchasing interest, while effective buzzer messages increase product visibility and user engagement, thereby encouraging purchase intention. This research contributes to understanding the role of brand image strategy and social influence on TikTok, providing insights for digital marketing efforts aimed at the platform's unique, highly interactive audience.